Sinkholes and the Engineering and Environmental Impacts of Karst: Proceedings of the Fourteenth Multidisciplinary Conference 2015
DOI: 10.5038/9780991000951.1054
|View full text |Cite
|
Sign up to set email alerts
|

Study on Monitoring and Early Warning of Karst Collapse Based on BOTDR Technique

Abstract: Brilliouin Optical Time Domain Reflectometer (BOT-DR) is a newly developed measurement and monitoring technique, which utilizes Brilliouin spectroscopy and Optical Time Domain Reflectometer (Jiang et al., 2006;Zhang et al., 2009;Xu et al., 2011) to measure strain generated in optical fibers as distributed in the longitudinal direction. This paper introduces the principle and characters of BOTDR technique firstly, and makes an example of karst collapse monitoring at section K14 of highway from Guilin to Yangshu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…However, they rely on sufficient coupling at the interface between the fibre and the soil, as well as an understanding of the logged strain profile at depth. Monitoring settlements and ground deformation using fibre optic cables is a recent technique (Guan et al, 2013;Klar et al, 2014;Guan et al, 2015;Zhang et al, 2016;Inaudi, 2017) that still requires further understanding and experience of soil-fibre interaction and its effect on the obtained data. The incorporation of fibre optic cables into earthworks could provide significantly improved information on the location, mechanisms, and magnitude of subsurface ground movements in real-time for newly built critical infrastructure over regions with high sinkhole susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, they rely on sufficient coupling at the interface between the fibre and the soil, as well as an understanding of the logged strain profile at depth. Monitoring settlements and ground deformation using fibre optic cables is a recent technique (Guan et al, 2013;Klar et al, 2014;Guan et al, 2015;Zhang et al, 2016;Inaudi, 2017) that still requires further understanding and experience of soil-fibre interaction and its effect on the obtained data. The incorporation of fibre optic cables into earthworks could provide significantly improved information on the location, mechanisms, and magnitude of subsurface ground movements in real-time for newly built critical infrastructure over regions with high sinkhole susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…In situ applications will however be subjected to temperature and moisture content changes, as well as vibrations from human activities (train, road, construction, etc. ), which will pollute the otherwise sensitive DFOS signal (Guan et al, 2015). Temperature changes can typically be corrected by adding a fibre that senses seasonal and daily changes in temperature on a specific channel of the interrogator (Kechavarzi et al, 2016), but this technique might not be sufficient at small strain levels, as needed for this particular application.…”
Section: mentioning
confidence: 99%
“…Three different fibre optic sensors were used, both independently and as part of a geogrid, in order to study the sensitivity of those sensor in detecting soil settlements. A recent development in sinkhole detection relies on the use of fibre optic cables, included in the earthwork during construction, sometimes within the use of a geogrid, to monitor ground displacements (Guan et al, 2013;Klar et al, 2014;Zhang et al, 2016;Guan et al, 2015;Inaudi, 2017). This is particularly adapted for long linear infrastructure, such as railways or roads.…”
Section: Introductionmentioning
confidence: 99%
“…Here, several collapse sinkholes have formed above caverns created by salt solution mining, threatening a major railway. Guan et al (2015) described a 90 m long BOTDR sinkhole monitoring system installed in the Guilin-Yangshuo highway, built upon cavernous limestone mantled by clayey soil. Jiang et al (2016) reported that the Chinese Institute of Karst Geology established in 2006 and 2012 two pilot monitoring sites at Guilin and Guigang of Guangxi province to monitor potential sinkholes along a highway and an oil pipe, respectively.…”
Section: Previous Experiencesmentioning
confidence: 99%
“…Recently, the potential societal risks associated with the construction of transport infrastructure (e.g., vulnerable high-speed railways) in vast sinkhole-prone areas are receiving special attention (Guan et al, 2015;Jiang et al, 2016). A key practical question is whether it would be possible to detect sinkhole-related deformation sufficiently in advance to prevent accidents.…”
Section: Introductionmentioning
confidence: 99%